Covid-19 and Nepali Labor Migration: Challenges and Changes - Gautam, Susmita; Mishra, Kunal (NUTA Journal, 2024)
Foreign labor migration is a cornerstone of global economic dynamics, significantly affecting both sending and receiving nations. This study examines the impact of the Covid-19 pandemic on foreign labor migration in Nepal, with a specific focus on the experiences of migrant workers returning through Tribhuvan International Airport. The economic importance of labor migration is underscored, particularly through remittances, which are crucial for the economy of Nepal. However, this sector is highly susceptible to external disruptions such as the pandemic. Despite its critical role, migrant workers often face numerous challenges and discrimination both abroad and upon their return to Nepal. This research aims to explore the effects of the Covid-19 pandemic on remittance flows, identify the challenges faced by returning migrant workers, and evaluate the effectiveness of social security provisions for these workers. Methodologically, the study employs a descriptive and analytical approach, combining qualitative and quantitative methods for comprehensive data collection and analysis. Utilizing purposive sampling, the research targets migrant workers returning through Tribhuvan International Airport. Data is gathered through questionnaires. The findings reveal significant disruptions caused by the pandemic, including employment instability, financial insecurity, and difficulties in accessing social protection and support services. Despite the resilience of migrant workers, they face heightened vulnerabilities exacerbated by the pandemic. The study concludes with recommendations aimed at policy reforms, enhanced support services, international collaboration, awareness campaigns, capacity-building initiatives, and ongoing research and monitoring.